Pratiques de régulation didactique en éducation physique et sportive. Deux études de cas contrastées - Jean-Marie Boudard; Fabienne Brière-Guenoun (Nantes Université, 2014)
The article focuses on the practices of didactic regulation of teachers in physical education. The research proposes to identify communications of two experienced teachers to identify learning objects, terms of regulation and what determines. The method is based on video recording and interview. We show that their practices regulations, in the study context, are very different quantitatively and qualitatively. This observation is the starting point for an inquiry into what determines these contrasts.